2016
DOI: 10.1177/1064804615611272
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Trust in Complex Automated Systems

Abstract: We studied the transparency of automated tools used during emergency operations in commercial aviation. Transparency (operationalized as increasing levels of explanation associated with an automated tool recommendation) was manipulated to evaluate how transparent interfaces influence pilot trust of an emergency landing planning aid. We conducted a low-fidelity study in which commercial pilots interacted with simulated recommendations from NASA’s Emergency Landing Planner (ELP) that varied in their ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 9 publications
1
30
0
Order By: Relevance
“…Accumulated research suggests that trust in automation is affected by system characteristics such as reliability degree of automation [16], [17], and transparency [10], [18], while individual characteristics such as self confidence in performing a task [19] culture [20], and environmental characteristics such as task load [21], [22] and risk [22] may affect either trust, dependence, or both.…”
Section: A Trust In Automationmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulated research suggests that trust in automation is affected by system characteristics such as reliability degree of automation [16], [17], and transparency [10], [18], while individual characteristics such as self confidence in performing a task [19] culture [20], and environmental characteristics such as task load [21], [22] and risk [22] may affect either trust, dependence, or both.…”
Section: A Trust In Automationmentioning
confidence: 99%
“…Annotating decisions with confidence judgments is another widely used technique for providing greater insight into system performance. This has been done variously by providing probabilities of success [10], [28], confidence in detection [28] F o r P e e r R e v i e w or confidence (Q values) in selected robot actions [11].…”
Section: Transparencymentioning
confidence: 99%
“…Research has shown that transparency methods in the form of decision rationale can increase trust for recommender systems in commercial aviation [7]. A replication of Lyons and colleagues [7] using a high-delity simulation found that added rationale increases user trust and reliance on the decision aid while reducing veri cation (i.e., second guessing) of the automation's recommendation [8]. Humans need to understand the logic behind any recommendations by a complex system.…”
Section: Trust and Transparency In Learning Systemsmentioning
confidence: 99%
“…Willingness to use automated or autonomous systems is highly related to trust, which may be influenced by various factors, such as system reliability, human predisposition to trust, prior and current experience, and many others. A growing literature suggests that trust significantly contributes to human decisions about the use of automation [1][2][3][4]. In other words, people tend to rely on automation they trust and not use automation they do not trust.…”
Section: Introductionmentioning
confidence: 99%